Clinical manifestations in POST-COVID-19 patients - Cibele P. Santos, Thalyta; Weryka S. Santos, Pammela; A. Souza, Samara; Henrique L. S. Santos, Pedro; S. Torres, Hevan; Eduarda C. B. Nascimento, Maria; F. Baptista, Abrahão; A. Hazime, Fuad (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: COVID-19 has significantly impacted the lives of individuals globally, as symp-toms can occur in both severe patients requiring intensive care and in patients with mild to moderate symptoms. Objective: To evaluate the clinical manifestations after COVID-19 in indi-viduals with and without comorbidities prior to infection by the new coronavirus. Methods: This was a cross-sectional observational study with a descriptive and analytical approach. One hundred and thirty-seven participants diagnosed with COVID-19 (3 to 12 months post-infection) of both sexes, aged between 18 and 59 years, underwent a clinical and functional evaluation to identify the late impacts of COVID-19, also known as “long COVID”. Results: The majority were female (n=103/75.2%) and brown (n=86/62.8%). The most common comorbidities were hyperten-sion (n=19/13.9%) and obesity (n=19/13.9%). The main post-infection symptoms were body pain (n=102/74.5%), cognitive impairment (n=53/38.7%), muscle weakness (n=59/43.1%) and hair loss (n=71/51.8%). There were significant differences between the groups without comorbidities (WCMG) and with comorbidities group (CMG) in mobility (p=0.03); labor productivity - pres-enteeism (p<0.05), total impairment at work (p=0.02) and impairment in activities of daily living (p<0.05); physical functionality (p=0.01) and subjective cognitive function (p<0.05). In the pulmo-nary function test, most participants had normal lung function (71.5%). Conclusion: Individuals with previous comorbidities have greater impairments in quality of life (mobility domain), rates of work impairment, and physical and cognitive functionality, when compared to patients without previous comorbidities.